PERAN MIKRO-INFLUENCER DALAM MENINGKATKAN BRAND AWARENESS UMKM MELALUI INSTAGRAM MARKETING: STUDI KASUS MALIQUE.PROJECT - Yulita, Rahma; Tinaria, Lisa (Jurnal Daya Saing, 2026)
This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, non-participant observation of Instagram content, and documentation in the form of screenshots of the account profile and collaborative posts. The informants consisted of the MSME owner, micro-influencers involved in collaborations, and Instagram audiences, with identities anonymized to maintain research ethics. Data were analyzed using thematic analysis, supported by source and technique triangulation to ensure data credibility.The findings indicate that micro-influencers play a significant role as visual representations of the brand by being positioned as muses or models in Instagram content, even without descriptive captions. Such visual representation implicitly communicates the brand’s aesthetic identity, service quality, and positioning, thereby contributing to organic brand awareness. This study concludes that micro-influencers function not only as promotional media but also as strategic actors in visual-based brand communication that is particularly relevant for MSMEs.